BASED ON THE WORKBENCH CONCRETE TRUCK MIXER BLADE STRESS ANALYSIS - GAO YaoDong; HU Xin (Jixie qiangdu)
Traditional method to calculate stress,concrete mixer truck mixing blades are usually of blade stirring power can be converted to uniformly distributed load,but due to the mixing blade in the process of acting force between concrete and is not evenly distributed,so that the calculation results have larger error. In order to accurately obtain the fluid load on the mixing blades. This study used the fluid-structure coupling analysis method,provided application of CFX and ANSYS Workbench numerical simulation analysis was carried out on the mixing blade,then it got the stress of mixing blade in the process of mixing and discharge,and compared with traditional stress analysis results. Analysis results show that the mixing blade root stress value,and the largest parts move biggest blade end,it offers the reliable basis for the intensity of the blade.